A Design Theory for Blockchain-Based Reputation Systems : Trust and Coordination in B2B Markets - Hemmrich, Simon
Keywords: Reputation Systems; Rating systems; monetary ratings; incentive mechanism; systems theory; Market coordination; advanced review system

Innovative lead-free ultrasonic bending transducers for low to medium power applications - Bornmann, Peter; Littmann, Walter; Scheidemann, Claus; Hemsel, Tobias
Nowadays ultrasound technology is established in various fields of application like industrial production or medical technology. Besides high power ultrasound applications like ultrasonic cleaning and ultrasonic welding, which are often not strongly restricted regarding their weight, costs, and construction space, there are many applications in the low to medium power range like handheld surgical instruments, medical inhalers, or ultrasonic cutters. For the latter there is often a strong demand for low weight and construction space and low costs to be competitive in mass production. Another challenge that arises from the RoHS-directive [1] is, that new ultrasonic devices should avoid the use of lead-containing PZT-materials. Against this background there is a demand for lead-free, small and lightweight and cost-effective ultrasonic transducers. In many of the above-mentioned applications, pre-stressed Bolted-Langevine-Transducers (BLT) based on lead-containing PZT-materials are established to generate ultrasonic vibrations. These are quite advantageous in many ways and can be built tailored to each application and even for high power of thousands of watts. But due to the required steps during their manufacturing process (machining parts, assembly, pre-stressing, frequency tuning, …), these transducers remain expensive. Furthermore, due to the operation in resonance, the construction space of these transducers is linked to their wavelength and cannot be reduced remarkably. For these reasons, our aim is to present an innovative lead-free ultrasonic transducer for low to medium power applications, that is based on bending vibrations instead of longitudinal vibrations. This design enables to build very small transducers. Furthermore, due to their simple construction, these transducers can be built at low manufacturing costs and are well suited for industrial mass production. The use of lead-free piezoelectric materials makes this transducer design ready for future applications. In our contribution we will present the model-based design of a lead-free 30 kHz bending transducer for applications up to 10 W. Furthermore, the comprehensive experimental analysis of this transducer-prototype in applications like mist generation or ultrasonic drilling will be presented. The results will be compared to a PZT-based bending transducer and a classical BLT to show the potential and limits of these kind of transducers and lead-free materials.

Power ultrasonic actuators with suddenly changing loads: How to control the amplitudes in resonance, antiresonance, or in-between - Littmann, Walter; Bornmann, Peter; Hemsel, Tobias; Scheidemann, Claus
Power ultrasonic actuators are used in various industrial, automotive and medical applications. Examples are ultrasonic welding of plastics or metal, surgery processes like cutting of tissue or bone, and the excitation of cavitation in liquids for ultrasonic cleaning. From a physical point of view, many of these processes are characterised by non-constant damping conditions for the ultrasonic actuators, since the systems need to be driven in unloaded as well as in high-loaded states. To get high power output, the piezoelectric actuators are usually driven in or near resonance at precisely defined vibration amplitudes. This is a quite complicated task especially if cost or mass optimized PZT transducers are used or if lead-free piezoelectric ceramics are applied to replace lead-containing materials. In particular the sudden change between loading states is very challenging for electronic excitation and control. The present contribution gives insight into typical problems that may arise in context with sudden load-changes during operation, e.g. uncontrolled jumps in voltage and velocity amplitudes. Measurements on ultrasonic power actuators being abruptly immersed into water at high amplitude are discussed for illustration. Observations during spontaneous load-changes are explained, and it is shown that several problems may be defused by driving the actuators in antiresonance or using a particular driving point in-between resonance and antiresonance (“falling edge control”). The different control strategies are investigated always using just one single hardware.

(mit K. Ruffing) Von Gerste, Göttern, Geld und Gesetzen. Eine Kultur- und Wirtschaftsgeschichte von Bier in der Antike

Semiramis - Droß-Krüpe, Kerstin (The Oxford Classical Dictionary)

Sardanapalus - Droß-Krüpe, Kerstin (The Oxford Classical Dictionary)

Frauenbilder und -rollen - Droß-Krüpe, Kerstin (Das achaimenidisch-persische Imperium)

Frauen als Gewalttäterinnen? Erste Überlegungen auf Basis von Petitionen aus dem griechisch-römischen Ägypten - Droß-Krüpe, Kerstin (Kriegerinnen im Altertum)

Atossa - Droß-Krüpe, Kerstin (Das achaimenidisch-persische Imperium)

What is Digital Fascism? - Fuchs, Christian (St. Anthony’s International Review)

Pasados presentes. La construcción de estereotipos de género en la recepción del mundo antiguo (Arenal. Revista de historia de las mujeres)

Sexuelle Bildung und (außer-)schulische Bildungspartner - Diederich, Julia; Magdeburg, Lena Maria (Sexuelle Bildung in der Grundschule und der universitären Lehrer*innenausbildung. Perspektiven aus Forschung, Praxis und Lehre)

BESCHREIBUNG DES R- UND DES TEMPERATUREINFLUSSES SOWIE DES EINLAUFVERHALTENS BEI EXPERIMENTELL BESTIMMTEN RISSFORTSCHRITTSKURVEN MIT DEM EXPONENTIALANSATZ - Kullmer, Gunter; Weiß, Deborah; Duffe, Tobias; Schramm, Britta; Ostwald, Richard

„Und ich hab’ euch jetzt mal ottos mops auf Englisch mitgebracht“ - Gedanken zu sprachlichen Ordnungen im ‚mehrsprachigen Literaturunterricht‘ - Büttner, Denise (Literarische Textualität und ästhetische Medialität in Deutsch als Zweitsprache (DaZ). Spannungsfelder – Potenziale – Perspektiven)

First impressions matter: Shaping the servicescape to address anonymity and trust in peer-to-peer sharing economy services - Kring-Ozuna, Edna (Journal of Service Management Research)
The increasing number of multi-unit hosts in peer-to-peer platforms such as Airbnb poses a significant challenge to single-unit hosts, who compete in a highly professionalized market where host-guest interactions have become increasingly anonymous. However, anonymity may undermine trust and affect eWOM, crucial elements for the performance of peer-to-peer platforms, as they heavily rely on mutual trust and positive eWOM to succeed. This study investigated the effects of the presence of hosts’ personal decorations and a local welcome gift on eWOM. Perceived anonymity and trust emerge as mediating mechanisms, such that the presence of personal decorations reduced the guest’s perception of anonymity towards the host, which subsequently increased guest’s trust and their intention to spread positive eWOM. The local welcome gift did not show any significant effects. These insights contribute to servicescape research and offer practical implications for single-unit hosts to differentiate their service experience from that of professional hosts.

Ultrasonic phased array interface using programmable I/O and microprocessor clock synchronisation - Nellius, Tom; Henne, Kevin; Hartinger, Maximilian; Meihost, Lars; Hetkämper, Tim; Zeipert, Henning; Claes, Leander; Henning, Bernd

ESEF-Berichterstattung in Deutschland: Herausforderungen und Chancen - Hofmann, Philipp; Sievers, Sönke; Li, Reeyarn
Diese Studie analysiert die ESEF-Berichterstattung in Deutschland seit der Einführung der iXBRL-basierten Berichtspflicht durch die ESMA im Jahr 2020. Anhand einer Stichprobe von 610 kapitalmarktorientierten Unternehmen der Frankfurter Börse im Zeitraum 2020-2023 wird gezeigt, dass 60,5% der Jahresabschlüsse die ESEF-Anforderungen vollständig erfüllen. Größere Unternehmen haben höhere Konformitätsraten als FSE-Scale und ausländische Unternehmen. Die Untersuchung der Taxonomie-Erweiterungen verdeutlicht, dass größere Unternehmen eher Erweiterungs-Tags nutzen, was mit Theorien freiwilliger Offenlegung übereinstimmt. Die verpflichtende Einführung des Anhang-Taggings im Jahr 2022 führte zu einer erhöhten Tagging-Granularität und verbesserter Offenlegungsqualität. Die Ergebnisse verdeutlichen Herausforderungen bei der ESEF-Umsetzung, wie Zugangsbarrieren und inkonsistente Durchsetzung, und geben Einblicke in unternehmensspezifische Offenlegungspraktiken im Kontext strukturierter Berichterstattung.

#frühförderung in Sozialen Medien – Zwischen Aufklärung, Empowerment, Optimierungsdruck und Vermarktung - Menzel, Tessa-Marie (Frühförderung interdiszipliniär)

Is Tax Transfer Pricing Harmonization a Panacea? Real Effects of Global Tax Transparency and Standards Consistency - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren (The Accounting Review)

How Much to Pay for Tax Certainty? The Role of Advance Tax Rulings for Risky Investment under Loss Offset and Tax Uncertainty - Chen, An; Hieber, Peter; Sureth-Sloane, Caren (International Tax and Public Finance)